Risky eating behaviors in young adults from two communes of the Ñuble region in Chile during covid-19 pandemic: Conductas alimentarias de riesgo en jóvenes adultos de dos comunas de la región de Ñuble en Chile durante pandemia covid-19 - Saéz-Opazo, Javiera (2023)
Objective: To analyze risky eating behaviors in relation to nutritional status and physical activity in young adults during the COVID-19 pandemic in the communes of Chillán and Chillán Viejo. Methods: Observational and cross-sectional design. A sample of 184 young adults of both sexes, who lived in two communes in the Ñuble region (Chile) during the period of confinement due to COVID-19 pandemic, was obtained. A personal history questionnaire and the SCOFF scale that assesses the risk of eating behavior disorders (EDs) were applied. Results: A 37.16% risk for ED was found (95% CI: 30.23 – 44.63%). The risk of eating behavior disorders was related to the variables: physical activity (p=0.01 bivariate analysis) and nutritional status (p=0.03, adjusted analysis). Conclusion: It was possible to identify a higher proportion than that recorded in the literature and the factors associated with eating disorders were those that were expected to be found.